Isolation of proteinaceous α-AMYLASE inhibitor from Bacillus pumilus NGP-1 - SHANMUGARAJU VEERAMUTHU; SURAYYA MOHAMMED; BIVYA GOPALAN (International Journal of Pharma and Bio Sciences, 2017)
The present study was conducted to screen the proteinaceous α-amylase inhibitory activity of Bacillus pumilus NGP-1. The culture free supernatant was precipitated by ammonium sulfate at 10-80% saturation for overnight at 4ºC. The precipitated proteins were desalted by dialysis and the protein content was estimated to be 1.3 mg/ml. The α-amylase inhibitory activity of partially purified proteinaceous α-amylase inhibitor was found to be 56%. The proteinaceous α-amylase inhibitor was characterized by Analytical High Performance Liquid Chromatography. The molecular weight of the α-amylase inhibitor was determined by Sodium Dodecyl Sulphate Polyacrylamide Gel Electrophoresis as 29kDa. The results suggested that the proteinaceous α-amylase inhibitor from Bacillus pumilus NGP-1 is first of its kind and may be an important candidate in research of diabetes.